ENHANCING INTEREST IN FAIRY TALES, STORIES, AND LITERARY WORKS AMONG PRIMARY SCHOOL STUDENTS (Web of Teachers: Inderscience Research, 2026)
This study explores methods to enhance primary school students’ interest in fairy tales, stories, and other literary works, emphasizing the role of narrative literature in cognitive, moral, and emotional development. The research employs a mixed-methods approach, combining literature review, classroom observations, and pedagogical interventions aimed at fostering engagement with literary texts. Findings indicate that interactive reading sessions, dramatization, collaborative storytelling, and guided discussion significantly improve students’ motivation, comprehension, and appreciation for literature. The study emphasizes the importance of culturally and pedagogically responsive methodologies to cultivate literacy, creativity, and a lifelong passion for reading among young learners.